2012
DOI: 10.3389/fnhum.2012.00155
|View full text |Cite
|
Sign up to set email alerts
|

High frequency deep brain stimulation attenuates subthalamic and cortical rhythms in Parkinson's disease

Abstract: Parkinson's disease (PD) is marked by excessive synchronous activity in the beta (8–35 Hz) band throughout the cortico-basal ganglia network. The optimal location of high frequency deep brain stimulation (HF DBS) within the subthalamic nucleus (STN) region and the location of maximal beta hypersynchrony are currently matters of debate. Additionally, the effect of STN HF DBS on neural synchrony in functionally connected regions of motor cortex is unknown and is of great interest. Scalp EEG studies demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
206
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(225 citation statements)
references
References 87 publications
17
206
2
Order By: Relevance
“…In addition, these authors proposed that broadband cortical gamma activity might maintain this abnormal coupling by feedback via the hyperdirect pathway from cortex to STN. Separately, Whitmer and colleagues (Whitmer et al 2012). However, the findings of Whitmer and colleagues were not reproducible across a larger patient sample, and in more extensive work de Hemptinne and colleagues showed that DBS reversibly reduced an exaggerated coupling between the phase of the beta rhythm and the amplitude of broadband activity in motor cortex (de Hemptinne et al 2015).…”
Section: Network Effects Of Subthalamic Nucleus Stimulationmentioning
confidence: 99%
“…In addition, these authors proposed that broadband cortical gamma activity might maintain this abnormal coupling by feedback via the hyperdirect pathway from cortex to STN. Separately, Whitmer and colleagues (Whitmer et al 2012). However, the findings of Whitmer and colleagues were not reproducible across a larger patient sample, and in more extensive work de Hemptinne and colleagues showed that DBS reversibly reduced an exaggerated coupling between the phase of the beta rhythm and the amplitude of broadband activity in motor cortex (de Hemptinne et al 2015).…”
Section: Network Effects Of Subthalamic Nucleus Stimulationmentioning
confidence: 99%
“…There is some evidence 2 that as Parkinson's destroys neurons in the basal ganglia, the activity of groups of cells in the STN and across this sensorimotor network becomes abnormally synchronized, locking at certain frequencies. DBS seems to release them from these activity patterns, as do some of the drugs that relieve Parkinson's symptoms 3,4 .…”
Section: 'Black Box' Beginningsmentioning
confidence: 99%
“…While Whitmer et al (2012)s showed that DBS in STN suppresses motor cortical beta band power, others showed no effect of DBS on beta (13-30 Hz) or broadband gamma (50-200 Hz) oscillations (de Hemptinne et al, 2013;Rowland et al, 2015). The only two available studies using MEG and testing PD patients ON and OFF DBS in resting state also showed no effect of beta power at rest, though gamma power (34-38 Hz) was affected by DBS (Cao et al, 2015(Cao et al, , 2017.…”
Section: Functional Importance Of Oscillations 241 Oscillations Inmentioning
confidence: 99%
“…Functionally, beta oscillations are thought to signal status quo while gamma activity is thought to underlie active processing in the underlying neuronal population (Fries, 2009;Manning et al, 2009;Engel and Fries, 2010). For instance, the enhanced beta-band oscillations in STN and motor cortex are accompanied by motor symptoms in PD (Pollok et al, 2012;Whitmer et al, 2012). Dopaminergic treatment and DBS suppress beta-activity and boost Background 32 Background gamma-activity in the STN and this is shown to correlate with better motor symptoms (Kühn et al, 2006.…”
Section: Functional Importance Of Oscillations 241 Oscillations Inmentioning
confidence: 99%
See 1 more Smart Citation